Diabetes as risk factor for pancreatic cancer: Hyperglycemia promotes epithelial-mesenchymal-transition and stem cell properties in pancreatic ductal epithelial cells. (28th February 2018) - Rahn, Sascha; Zimmermann, Vivien; Viol, Fabrice; Knaack, Hendrike; Stemmer, Kerstin; Peters, Lena; Lenk, Lennart; Ungefroren, Hendrik; Saur, Dieter; Schäfer, Heiner; Helm, Ole; Sebens, Susanne
Abstract: Type 2 diabetes mellitus (T2DM) is associated with hyperglycemia and a risk to develop pancreatic ductal adenocarcinoma (PDAC), one of the most fatal malignancies. Cancer stem cells (CSC) are essential for initiation and maintenance of tumors, and acquisition of CSC-features is linked to epithelial-mesenchymal-transition (EMT). The present study investigated whether hyperglycemia promotes EMT and CSC-features in premalignant and malignant pancreatic ductal epithelial cells (PDEC). Under normoglycemia (5 mM d -glucose), Panc1 PDAC cells but not premalignant H6c7-kras cells exhibited a mesenchymal phenotype along with pronounced colony formation. While hyperglycemia (25 mM d -glucose) did not impact the mesenchymal phenotype of Panc1 cells, CSC-properties were aggravated exemplified by increased Nanog expression and Nanog-dependent formation of holo- and meroclones. In H6c7-kras cells, high glucose increased secretion of Transforming-Growth-Factor-beta1 (TGF-β1) as well as TGF-β1 signaling, and in a TGF-β1-dependent manner reduced E-cadherin expression, increased Nestin expression and number of meroclones. Finally, reduced E-cadherin expression was detected in pancreatic ducts of hyperglycemic but not normoglycemic mice. These data suggest that hyperglycemia promotes the acquisition of mesenchymal and CSC-properties in PDEC by activating TGF-β signaling and might explain how T2DM facilitates pancreatic tumorigenesis. Highlights: Elevated glucose levels aggravate cancer stemness in pancreatic cancer cells. Hyperglycemia essentially impacts already on pancreatic ductal epithelial cells. Hyperglycemia-induced mesenchymal and CSC-properties are TGF-β1 dependent. This study gives insight how hyperglycemia contributes to pancreatic tumorigenesis.